Implementing Role Play in English Speaking Class: A Descriptive Case Study - Nila Dharmayanti Situmorang; Elih Sutisna Yanto; Iwan Ridwan (FKIP - Universitas Riau, 2026)
Speaking anxiety remains a persistent barrier for Senior High School EFL students, limiting their ability to communicate effectively in English. This study explored implementation of role play as a teaching strategy to enhance speaking skills and reduce anxiety through real-life situational practice using AI character. Conducted at a Senior High School in Karawang, the study involved 26 students from class XI IPA 3, this study employed qualitative method and used a case study design. Researcher used triangulation method to collect the data including classroom video recordings, semi-structured interviews, and questionnaires. Findings reveal that the integration of structured role play activities increased students' motivation, speaking fluency, and self-confidence. The data showed that 73.1% students agreed role play increased their participation in learning process, while 15 out of 26 students reported feeling confident during English speaking activities. In addition, 13 students reported improvements in their pronunciation, 6 students reported enhancements in their fluency, and 16 students recognized better mastery of vocabulary. Students responded positively to the interactive learning process. This study concluded that role play activities with a structured framework through real-life contexts is an effective learning method to enhance speaking skills and reduce anxiety for EFL students.